Significantly conquering moisture-induced luminescence quenching of red line-emitting phosphor Rb2SnF6:Mn4+ through H2C2O4 triggered particle surface reduction for blue converted warm white light-emitting diodes. Issue 2 (30th November 2018) - Jiang, Chunyan; Brik, Mikhail G.; Srivastava, Alok M.; Li, Lihua; Peng, Mingying
Abstract : A highly stable red phosphor Rb2 SnF6 :Mn 4+ is achieved by appropriate reduction treatment using a low concentration of H2 C2 O4 . Abstract : Mn 4+ doped fluoride phosphors have attracted tremendous attention in the solid-state lighting field due to the outstanding feature of efficient narrow band red emission. However, poor resistance against moisture-induced luminescence quenching is a recognized obstacle for realizing their wider commercial use. Herein, we design and fabricate a highly stable red phosphor based on previously unnoticed Rb2 SnF6 :Mn 4+, which, estimated by the single crystal X-ray diffraction data, crystallizes in the trigonal space group P 3̄ m 1 with the lattice parameters a = b = 6.0323(12) Å, c = 4.7880(8) Å, and V = 150.89(7) Å 3 . The Rb2 SnF6 :Mn 4+ as expected exhibits highly efficient red emission upon excitation by UV and blue light. Significantly, the poor water resistance is conquered by constructing a protective deactivated layer with surface reduction of Mn 4+ . A treatment solution with appropriate reducing ability is emphasized to obtain Rb2 SnF6 :Mn 4+ with simultaneous high brightness and water resistance. The results show that the low concentration of H2 C2 O4 solution treated Rb2 SnF6 :Mn 4+ preserves a bright red-emitting color analogous to its initial color and >95% of its initial emission intensity when immersing in water at room temperature (RT) and in boiling water for 3 h. Lastly, by employing H2 C2 O4 treated Rb2 SnF6 :Mn 4+ as a red phosphor, a high quality WLED with a CRI of 90, CCT of 3936 K and luminous efficacy of 106.24 lm W −1 is fabricated. This work not only experimentally fabricates a new efficient and stable Rb2 SnF6 :Mn 4+ phosphor that can be used for high performance warm WLEDs but also provides a deep insight into how to well address moisture-induced Mn 4+ luminescence quenching through appropriate reduction of Mn 4+, opening up new opportunities for future solid-state lighting purposes.